2013
DOI: 10.1073/pnas.1222568110
|View full text |Cite|
|
Sign up to set email alerts
|

Stable isotope-based diet reconstructions of Turkana Basin hominins

Abstract: Hominin fossil evidence in the Turkana Basin in Kenya from ca . 4.1 to 1.4 Ma samples two archaic early hominin genera and records some of the early evolutionary history of Paranthropus and Homo . Stable carbon isotopes in fossil tooth enamel are used to estimate the fraction of diet derived from C 3 or C 4 resources in these hominin taxa. The earliest hominin species in the Turkana Basin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
179
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 60 publications
12
179
0
Order By: Relevance
“…Levin et al (4) found the isotopic composition of many mammalian taxa from Woranso-Mille to be in accordance with both field observations and previously reported data, in which giraffes, on one hand, and Alcelaphines and other presumed grass grazers, on the other hand, consistently occupied the two end points of the mammalian carbon isotopic spectrum (C 3 -and C 4 -dominated). Such observations confirm suggestions that diagenesis is not playing any obvious role in the carbon isotopic composition of wellselected tooth enamel (11,12) (Fig. 1A).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Levin et al (4) found the isotopic composition of many mammalian taxa from Woranso-Mille to be in accordance with both field observations and previously reported data, in which giraffes, on one hand, and Alcelaphines and other presumed grass grazers, on the other hand, consistently occupied the two end points of the mammalian carbon isotopic spectrum (C 3 -and C 4 -dominated). Such observations confirm suggestions that diagenesis is not playing any obvious role in the carbon isotopic composition of wellselected tooth enamel (11,12) (Fig. 1A).…”
supporting
confidence: 88%
“…What is more, the conclusions of Levin et al (4) are consistent with the recently published eastern African stable isotopic dataset (11)(12)(13). These papers had already presented tantalizing evidence that separated Australopithecus afarensis from Australopithecus anamensis based on their carbon isotopic composition, despite their morphological similarities (Fig.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Tooth enamel from modern baboons from Africa, including P. anubis and P. hamadryas, have an average δ 13 C 1750 value of −10.2 ± 2.7‰ (n = 36; maximum = −2.5‰; minimum = −15.5‰) (data in ref. 28), corresponding to a ca. 15 ± 20% C 4 -based diet; the diets of modern baboons are very different from T. brumpti or T. oswaldi ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We discuss Theropithecus in the context of C 3 -and C 4 -derived diet resources and the overall context of isotope ecology in the Turkana Basin. The diet of Theropithecus is of interest compared with the diets of early hominins (26,28) from the same deposits; hominins exhibit a change in the use of C 4 resources over this time interval, and thus, these primates were in potential competition for dietary resources.…”
mentioning
confidence: 99%